The debate over the legislation on women's equality in Costa Rica (1984-1990) - Ugalde Quesada, Alexia (2021)
This article explores the introduction of ideas about women’s equality in Costa Rica during the 1980s, by offering a reconstruction of the debate that arose after the presentation of the Bill on Real Equality for Women and identifying the sectors that supported and opposed this bill, their speeches and arguments. Moreover, the article recovers memories of the struggle that led to the approval of the Law for the Promotion of Social Equality of Women in 1990, identifying political strategies implemented for dissemination, promotion and pressure. It is concluded that in 1984, with the ratification of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) by the Costa Rican government, and throughout the 1985 electoral campaign, the issue of women’s equality began to occupy political discussions in the country, because of the international processes that promoted the creation of new legislation, but also the organization of women’s and feminist movements.